1997
DOI: 10.1088/0031-9155/42/7/011
|View full text |Cite
|
Sign up to set email alerts
|

Design and calibration of electric field probes in the range 10 - 120 MHz

Abstract: In view of potential thermal hazards, there is a need to determine the specific absorption rate (SAR) distributions associated with radiofrequency coils used in magnetic resonance imaging (MRI) (typically 10-120 MHz). Electric field (E-field) distributions in tissue-equivalent phantoms may be determined using a probe comprising a dipole antenna and a detector. The geometry of the dipole dictates the sensitivity of the device, thus two designs are discussed in this paper. Both probes are compact, have a spatial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 4 publications
0
13
0
Order By: Relevance
“…Results (E-field magnitude, SAR) using these standardized models were compared with other FDTD codes and other computational methods as part of the European Cooperation in the field of Scientific and Technical Research (COST) programme (31,32). Verification of the code for applications in clinical hyperthermia has also been made (33) and recently we have further verified the use of this code by comparing numerically predicted E-fields due to a rectangular coil in a phantom experiment with those measured using a calibrated minimally perturbing E-field probe in an identical experiment (24,34).…”
Section: Electromagnetic Modelingmentioning
confidence: 93%
“…Results (E-field magnitude, SAR) using these standardized models were compared with other FDTD codes and other computational methods as part of the European Cooperation in the field of Scientific and Technical Research (COST) programme (31,32). Verification of the code for applications in clinical hyperthermia has also been made (33) and recently we have further verified the use of this code by comparing numerically predicted E-fields due to a rectangular coil in a phantom experiment with those measured using a calibrated minimally perturbing E-field probe in an identical experiment (24,34).…”
Section: Electromagnetic Modelingmentioning
confidence: 93%
“…This makes the task of quantification of RF heating (SARs and temperature rises) and its correlation with the electric field more difficult as precise measurement techniques, and rigorous [16] computational methods are required for their evaluation. As MRI RF induced SARs and power deposition in tissues have been reported by many authors [9,[17][18][19][20] using computational electromagnetics, these calculations/simulations along with electric field [16,21,22] and RF heating measurements [23,24] have confirmed temperature changes in biological samples during MRI scans. In this context, the fluorooptic techniques, for instance, have shown that they are capable of relatively accurate temperature measurements [25].…”
Section: Introductionmentioning
confidence: 62%
“…1. A dipole antenna based probe [22] was built and optimized for measuring the E 1 field intensities at 340 MHz. Using this E 1 field probe, one Cartesian component of the E 1 field distribution was mapped inside the cylindrical phantom loaded in the coil and inside the empty coil.…”
Section: Experimental E 1 Field Estimationmentioning
confidence: 99%
See 1 more Smart Citation
“…Although electrical field probes have been studied over a long period, only one group reported on the sensitivity of their diode electrical field probe in a 'biological' equivalent tissue. Taylor et al 8 calibrated their E-field probe in a water filled TEM cell. They used a rectangular dipole probe with a BAT-17 surface mount diode and tested it in the frequency range of 10-120 MHz using field strengths from 10-120 V/ m. From the values reported, a sensitivity of 0.54 (V/m)/(V/m) could be calculated which was more or less independent of the frequency in the range of 20-120 MHz.…”
Section: Discussionmentioning
confidence: 99%